Microsurgical anatomy of the posterior median septum of the human spinal cord. Issue 1 (1st December 2014) - Turkoglu, Erhan; Kertmen, Hayri; Uluc, Kutluay; Akture, Erinc; Gurer, Bora; Cikla, Ulaş; Salamat, Shahriar; Başkaya, Mustafa K.
<x xml:space="preserve">Abstract</x> The aim of this study was to analyze the topographical anatomy of the dorsal spinal cord (SC) in relation to the posterior median septum (PMS). This included the course and variations in the PMS, and its relationship to and distance from other dorsal spinal landmarks. Microsurgical anatomy of the PMS was examined in 12 formalin‐fixed adult cadaveric SCs. Surface landmarks such as the dorsal root entry zone (DREZ), the denticulate ligament, the architecture of the leptomeninges and pial vascular distribution were noted. The PMS was examined histologically in all spinal segments. The PMS extended most deeply at spinal segments C7 and S4. This was statistically significant for all spinal segments except C5. The PMS was shallowest at segments T4 and T6, where it was statistically significantly thinner than at any other segment. In 80% of the SCs, small blood vessels were identified that traveled in a rostrocaudal direction in the PMS. The longest distance between the PMS and the DREZ was at the C1–C4 vertebral levels and the shortest distance was at the S5 level. Prevention of deficits following a dorsal midline neurosurgical approach to deep‐seated SC lesions requires careful identification of the midline of the cord. The PMS and septum define the midline on the dorsum of the SC and their accurate identification is essential for a safe midline surgical approach. In this anatomical study, we describe the surface anatomy of the dorsal SC and its relationship with the PMS, which can be used to determine a safe entry zone into the SC. Clin. Anat. 28:45–51, 2015. © 2014 Wiley Periodicals, Inc.